Carbohydrates observations in suburb Nanjing, Yangtze River of Delta during 2017–2018: Concentration, seasonal variation, and source apportionment. (15th December 2020) - Li, Wenjing; Wang, Ming; Chen, Mindong; Hu, Kun; Ge, Xinlei; Nie, Dongyang; Gu, Chuanxin; Yu, Wentao; Cheng, Yueming
Abstract: The temporal characteristic and source apportionment analyses on carbohydrates in this study are useful for understanding PM2.5 sources in Yangtze River Delta (YRD) region. Carbohydrates are important consistent of primary organic aerosol (POA) and some of them are widely used as tracers for source apportionment of fine particle (PM2.5 ). In this study, ambient concentrations of 10 carbohydrates (levoglucosan, arabitol, mannitol, sucrose, fructose, glucose, inositol, threitol, 2-methyl-threitol, and trehalose) in PM2.5 at a suburb site of Nanjing during 2017–2018 were quantified by a high-performance liquid chromatography tandem mass spectrum/mass spectrum (HPLC-MS/MS). Among all measured carbohydrates, Levoglucosan, with the average concentration of 337.6 ng m −3, was the dominant one, contributing 89% of the total 10 carbohydrates concentration. The concentration of levoglucosan in 2017 was 412.4 ng m −3, higher than that of 2018 (232.5 ng m −3 ). Similarly, the average concentration for other 9 carbohydrates was 43.6 ng m −3 in 2017, slightly higher than 2018 (38.32 ng m −3 ). Levoglucosan concentrations presented a similar seasonal variation in both 2017 and 2018, which values were high in winter and autumn, and went down in summer and spring. As for the other 9 carbohydrates, their overall concentrations presented different seasonal variation patterns between 2017 and 2018. During 2017, their concentrations were the highest in summer, followed by spring, autumn, and winter. However, the richest concentrations occurred in spring, followed by autumn, summer and winter during 2018. Positive matrix factorization (PMF) model was then applied for sources apportionment of carbohydrates. Seven sources were identified, including airborne pollen, fungal spores and soil dust, plants debris, biomass burning, biogenic secondary organic aerosol (SOA), threitol-rich source, and inositol-rich source. Biomass burning contributed the most to the measured concentrations of 10 carbohydrates, with relative contribution of 57.9%, followed by airborne pollen (12.9%), 2-methyl-threitol rich source (10.0%), fungal spores and soil dust (9.4%), plant debris (6.3%), threitol-rich source (2.4%), and inositol-rich source (1.1%). Relative contributions of biomass burning showed a significant decrease from 68.8% in 2017 to 50% in 2018, suggesting that biomass burning in YRD region was well controlled in 2018 compared to 2017. Highlights: Two-years carbohydrates in Nanjing were quantified by HPLC-MS/MS. Seasonal variations of each carbohydrates were conducted in past two years. Source apportionment were applied to analyze the sources of carbohydrates in Nanjing.